2018
DOI: 10.1089/end.2017.0811
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Dynamic Analysis of Hand-Pump Infuser and UROMAT Endoscopic Automatic System for Irrigation Through a Flexible Ureteroscope

Abstract: The flow rates of irrigation produced by the HP and the E.A.S.I. pump are similar at pressures of 150 and 200 mm Hg irrespective of the occupancy of a ureteroscope's working channel during the first 5-minutes of irrigation. Irrigation pressure at the entry site of the ureteroscope is subject to significant variability with use of the HP compared to the E.A.S.I. pump irrigation system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 20 publications
0
18
0
2
Order By: Relevance
“…The irrigation inflow from the tip of the working channel in the fURS depends on the irrigation method used. Although a hand‐ or foot‐activated syringe‐based irrigation system might produce a drastic increase of inflow through the working channel, which influences the intrarenal pressure, and pressurized irrigation bags in which the irrigation pressure gradually decreases cannot maintain constant irrigation flow during the procedure over time, as well as natural gravity‐based irrigation adjusted by the height of the saline bag, the AIP maintains a constant irrigation flow for most of the procedure . In the present study, the efficiency of irrigation flow in gravity‐based irrigation under the same pressure was significantly lower than one of the two AIPs because of the loss of pressure power due to gradually decreasing the height of the saline surface, changing the pipe diameter in the middle of the irrigation tube.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…The irrigation inflow from the tip of the working channel in the fURS depends on the irrigation method used. Although a hand‐ or foot‐activated syringe‐based irrigation system might produce a drastic increase of inflow through the working channel, which influences the intrarenal pressure, and pressurized irrigation bags in which the irrigation pressure gradually decreases cannot maintain constant irrigation flow during the procedure over time, as well as natural gravity‐based irrigation adjusted by the height of the saline bag, the AIP maintains a constant irrigation flow for most of the procedure . In the present study, the efficiency of irrigation flow in gravity‐based irrigation under the same pressure was significantly lower than one of the two AIPs because of the loss of pressure power due to gradually decreasing the height of the saline surface, changing the pipe diameter in the middle of the irrigation tube.…”
Section: Discussionmentioning
confidence: 55%
“…compared hand‐pump infusers, such as pressurized irrigation bags, versus the UROMAT E.A.S.I. with respect to the irrigation flow rate from the working channel in the fURS . They found that the irrigation flow using a hand‐pump infuser decreased as time passed, whereas the UROMAT E.A.S.I.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations